What is Fuzzy About Clustering in West Africa? - Qureshi, Mahvash (IMF Working Papers; Working Paper ;, 2006)
Applying techniques of clustering analysis to a set of variables suggested by the convergence criteria and the theory of optimal currency areas, this paper looks for country homogeneities to assess membership in the existing and proposed monetary unions of the broader west African region. Our analysis reveals considerable dissimilarities in the economic characteristics of the countries in west and central Africa. In particular, the West African Monetary Zone (WAMZ) countries do not form a cluster with the West Africa Economic and Monetary Union (WAEMU) countries; and, within the WAMZ, there is a significant lack of homogeneity. Furthermore, when west and central African countries are considered together, we find significant heterogeneities within the CFA franc zone, and some interesting similarities between the Economic and Monetary Community of Central Africa (CEMAC) and WAMZ countries. Overall, our findings raise some questions about the geographical boundaries of several existing and proposed monetary unions.